2005
DOI: 10.4049/jimmunol.174.5.2612
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Dendritic Cells Have Both Antigen Presenting and Lytic Function and in Response to CpG Produce IFN-γ via Autocrine IL-12

Abstract: We have isolated rare cells bearing the NK cell surface marker NK1.1, as well as the dendritic cell (DC) marker CD11c, from the spleen, liver, lymph nodes, and thymus of normal mice. These cells possess both NK cell and DC function because they can lyse tumor cells and subsequently present Ags to naive Ag-specific T cells. Interestingly, in response to IL-4 plus either IL-2 or CpG, NKDC produce more IFN-γ than do DC, or even NK cells. We determined that CpG, but not IL-2, induces NKDC to secrete IFN-γ via the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
133
3
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(152 citation statements)
references
References 38 publications
(29 reference statements)
11
133
3
2
Order By: Relevance
“…They are characterized by the production of large amounts of IFN-g secretion in response to a combination of CpG þ IL-4 or IL-12 þ IL-18. 55,58 Hence, the authors demonstrated that contamination of DC preparations with NKDCs accounted for the controversial production of IFN-g by DCs. More interestingly, the authors showed that, subsequent to OVA-loaded YAC-1 cell killing, NKDCs up-took and presented OVA antigen to specific class-I restricted T cells, thus claiming the benefit of these cells to kill their target and directly cross-present resultant antigen to specific T cells.…”
Section: Identification Of Killer DC Subsets: Nkdcs Versusmentioning
confidence: 99%
See 3 more Smart Citations
“…They are characterized by the production of large amounts of IFN-g secretion in response to a combination of CpG þ IL-4 or IL-12 þ IL-18. 55,58 Hence, the authors demonstrated that contamination of DC preparations with NKDCs accounted for the controversial production of IFN-g by DCs. More interestingly, the authors showed that, subsequent to OVA-loaded YAC-1 cell killing, NKDCs up-took and presented OVA antigen to specific class-I restricted T cells, thus claiming the benefit of these cells to kill their target and directly cross-present resultant antigen to specific T cells.…”
Section: Identification Of Killer DC Subsets: Nkdcs Versusmentioning
confidence: 99%
“…In mice, two subsets of cells with bitypic NK and DC phenotypic and functional characteristics have been recently discovered and termed NKDCs and interferonproducing killer DCs (IKDCs). 55,56,78 It remains unclear how closely related these two subsets are or whether they are indeed identical. The phenotypic and functional characteristics of both subsets are summarized in Table 2.…”
Section: Identification Of Killer DC Subsets: Nkdcs Versusmentioning
confidence: 99%
See 2 more Smart Citations
“…1 IKDCs, through a direct tumoricidal activity, have been implicated in the innate immunotherapeutic effects of a combination of interleukin (IL)-2 plus imatinib against B16F10-derived melanomas. 2 Previous reports had also postulated the existence of a population of cells sharing some of the functional and phenotypical features of both NK cells and DCs in mice, 3 mainly on the basis of CD11c and NK1.1 coexpression. There is evidence that these so-called NKDCs (that comprise the IKDC subset) play an important role in the defense against Listeria primarily by producing IFN-g in response to IL-12 and IL-18.…”
Section: Introductionmentioning
confidence: 99%